Risk assessment in paediatric glioma—Time to move on from the binary classification. (March 2017) - Dodgshun, A.J.; Hansford, J.R.; Sullivan, M.J.
Highlights: Paediatric glioma encompasses a broad spectrum of disease with highly variable prognoses. Consistent risk factors affecting prognosis are well established for high-grade and low-grade glioma. Risk classification for paediatric glioma is possible and should be pursued. Abstract: Background: Paediatric glioma encompasses a wide range of entities with highly variable prognoses. Gliomas are grouped by histopathological features into high- and low-grade glioma but this classification until recently has not taken into account many emerging risk factors in this disease. A comprehensive risk classification has not been published for paediatric glioma despite many risk factors being established in this disease. Methods: A comprehensive literature review was carried out identifying risk factors for paediatric low-grade and high-grade glioma. Results: The most consistently described risk factors in high-grade glioma included midline location and extent of surgical resection. For patients with progressive unresectable low-grade glioma, age under 1, neurofibromatosis type I status and location were the most consistently prognostic. Molecular classification shows promise in accurately reassigning diagnosis for some gliomas. Conclusion: Risk profiling in paediatric glioma will require a focused multinational effort but will result in a more accurate and nuanced assessment of prognosis.